Kajian Teknis Geometri Peledakan untuk Mendapatkan Fragmentasi dan produksi yang Optimum di Lokasi Penambangan Batu Gamping Area 242,IUP 329 Bukit Tajarang,PT. Semen Padang. - Aulia Rahman, M Fajri Aulia Rahman; Farid, Faizar; Ikrar Lagowa, Muhammad (JTK (Jurnal Teknik Kebumian), 2023)
In the mining process with hard rock, it is necessary to blast (blasting) which aims to scatter the rock, so that it can facilitate digging activities. The success of the explosion process can be seen in the rock fragmentation resulting from the explosion. The purpose of this research is to determine the actual blast geometry used in the field, to determine the size of the fragmentation and blast results based on the geometry used, to determine the effective explosion geometry so that the fragmentation and production results of the explosion carried out by PT Semen Padang meet the crusher. From the results of research and calculations in the field, it was found that PT Semen Padang used two types of blasting geometry, namely geometry with loads and spacing of 3 x 4 and 4 x 5 with an average hole depth of 10 m, stemming 4 m, and the length of the filling, namely 6 m. In geometry with loads and spacing of 3 x 4, the average result of F80 fragmentation on an 80 cm screen is 61.72 cm and with an average tonnage volume of rock uncovered 24,400 tons/day, while in the geometry of 4 x 5 the average yield is obtained. Fragmentation of F80 on a 80 cm screen is 89.5 cm and with an average tonnage volume of rock uncovered 28,210 tons/day. It is necessary to change the blasting geometry used in order to achieve 80 cm F80 fragmentation results and meet the required production of 30,000 tons/day